"Critico a publicidade e vivo dela": Cartografia de movimentos contra-hegemônicos internos ao campo da publicidade - Schuch, Lucas Alves (2024)
This thesis is focused on the field of advertising, especially analyzing the behavior of advertising professionals who strain their own space to review certain practices that do not dialogue with the spirit of contemporary times. We built our rhizome from Deleuzian thought, in the search to answer the following problem: What are and how are counter-hegemonic movements organized in the production pole of the advertising field and how are they influencing (and being influenced) by the current professional habitus? To theoretically elaborate this problem, we used Bourdieu's work with his notions of field, capitals and habitus, which allowed us to visualize the structure in which professionals are inserted. Power relations were analyzed from the perspective of Foucault, Deleuze and Bourdieu. Finally, the notions of hegemony and counter-hegemony are based on Antônio Gramsci and Raymond Williams, respectively. Methodologically, our cartography has different production and data collection techniques, but the quantitative steps stand out, in a structured questionnaire applied to 825 professionals in the field, bringing 95% of data reliability. In addition to a qualitative stage, with in-depth interviews with 9 professionals from the field, identified by this counter-hegemonic posture that we are describing. In this thesis it was possible to identify characteristics of this possible trait of the counter-hegemonic habitus, as well as a list of initiatives, movements and collectives that reveal this posture in the field of advertising. These counter-hegemonic movements are, for the most part, organized to promote transformations in a field so lacking in revision in the search for better working conditions. Among the main characteristics of this counter-hegemonic posture found in this study, the vocalization of problems stands out; criticism always negotiated in terms of employability and privileges; and also diversity and belonging to underrepresented groups as a point of aggregation of critical people.